Fabrication of Single Chamber Microbial Fuel Cell (SMFC) Using Soil as a Substrate - Siti Kudnie, Sahari; Mohd. Zulhilmi, Firdaus Rosli; Amir Maina, Butit; Kuryati, Kipli; Martin, Anyi; Asmahani, Awang; Marini, Sawawi; Mohamad Rusop, Mahmood; Lilik, Hasanah; Abdul Rahman, Kram; Zaidi, Embong; Hafsah, Nahrawi (Universiti Putra Malaysia, 2022)
This paper presents a Single-chamber Microbial Fuel Cell (SMFC) design by utilizing soil as a substrate with two sets of electrode combinations, which are graphite-activated carbon and copper-zinc of different sizes. It was found that graphite and activated carbon produced greater power density compared to copper and zinc. Moreover, it was observed that the graphite-activated carbon cloth electrode with a bigger surface area of 51cm2 resulted in a higher power density of 904mW/m2 . To further improve the voltage production of this model, four SMFCs were stacked in series and connected to a DC-DC boost converter to increase the voltage to 1.482 V for the copper-zinc electrode and 1.722 V for the graphite-activated carbon electrode, respectively, which was sufficient to light up an LED light.